REFORMASI PENGELOLAAN MINYAK DAN GAS BUMI BERDASARKAN KONSTITUSI; STUDI KASUS WILAYAH KERJA MASELA MALUKU - Yusa' Farchan (Jurnal Renaissance, 2016)
This research besides study whether the management and culvation oil and gas in the Masela Block in accordance with rules in the article of  33  the constitution of 1945, it also examines at how the management of the Masela Block to increase state revenues and public welfare. This research using qualitative methods with the approach case study. In full view of the perspective of contract system and the power mining, management in Masela Block it can be uttered not based on conception “in all over the state”  in accordance with rules of  the constitution . Operation the Masela Block by Inpex Corporation, is not state control on the first rank, because state in fact has not been conducted directly management natural resources the oil and gas. Although Production Sharing Contract system used, believed to be a model contracts accommodate the article of 33 the constitution of 1945, but in practice, the state could not do mastery entirely in the Masela Block. The state potentially losing sovereignty in managing all of economic resources oil and gas in the Masela Block, because mastery itself be turned over or authorized to corporate or form permanent business. It is required to reform governance regional development in the Masela Block which includes; first, to ensure how big state revenues; second, to ensure the realization of welfare the local community and regional economic progress; third, to ensure  the involvement of National Oil Company (NOC)  Indonesia, which is that  PT. Pertamina; fourth, keep investment climate.Key Words: Masela Block; management of oil and gas.